Borneol, a Bicyclic Monoterpene Alcohol, Reduces Nociceptive Behavior and Inflammatory Response in Mice - Jackson Roberto Guedes da Silva Almeida; Grasielly Rocha Souza; Juliane Cabral Silva; Sarah Raquel Gomes de Lima Saraiva; Raimundo Gonçalves de Oliveira Júnior; Jullyana de Souza Siqueira Quintans; Rosana de Souza Siqueira Barreto; Leonardo Rigoldi Bonjardim; Sócrates Cabral de Holanda Cavalcanti; Lucindo José Quintans Junior (The Scientific World Journal)
Borneol, a bicyclic monoterpene, has been evaluated for antinociceptive and anti-inflammatory activities. Antinociceptive and anti-inflammatory activities were studied by measuring nociception by acetic acid, formalin, hot plate, and grip strength tests, while inflammation was prompted by carrageenan-induced peritonitis. The rotarod test was used to evaluate motor coordination. Borneol produced a significant (P<0.01) reduction of the nociceptive behavior at the early and late phases of paw licking and reduced the writhing reflex in mice (formalin and writhing tests, resp.). When the hot plate test was conducted, borneol (in higher dose) produced an inhibition (P<0.05) of the nociceptive behavior. Such results were unlikely to be provoked by motor abnormality. Additionally, borneol-treated mice reduced the carrageenan-induced leukocytes migration to the peritoneal cavity. Together, our results suggest that borneol possess significant central and peripheral antinociceptive activity; it has also anti-inflammatory activity. In addition, borneol did not impair motor coordination.